TYPHUS FEVER IN MEXICO ASTUDY OF EPIDEMIOLOGY BY MEANS OF COMPLEMENT FIXATION - VARELA, GERARDO; PLOTZ, HARRY; ORTIZ MARIOTTE, CARLOS; FREEMAN, GUSTAVE (INSTITUTO DE SALUBRIDAD Y MEDICINA TROPICAL, CD. MEXICO, DF, MEX, 1908)
Any combination of acid hydrolysis and oxidation can activate the carbohydrate: there is no specific agent The best results were with chromic acid The suggestion is made that periodic acid hydrolysis can yield equally good results in shorter time Ammon
AM J TROP MED
Keywords: TYPHUS, FEVER, MEXICO, STUDY, EPIDEMIOLOGY, MEANS; CIENCIAS MEDICAS; MEDICINA INTERNA; ENFERMEDADES INFECCIOSAS